Treatment outcomes and prognostic factors for non- malignancy associated secondary hemophagocytic lymphohistiocytosis in children - Hua Pan; Gaoyan Wang; Enben Guan; Liang Song; Aiqin Song; Xiaodan Liu; Zhi Yi; Li-rong Sun (BMC, 2020)
Abstract Background Secondary hemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory syndrome that requires prompt diagnosis and appropriate treatment. A risk-stratification model that could be used to identify high-risk pediatric patients with HLH who should be considered for second-line therapies, including salvage regimens and allogeneic hematopoietic cell transplantation (HCT), was developed. Methods The medical records of 88 pediatric patients (median age 1.4 years, range 0.2-15 years) with non-malignancy associated secondary HLH were retrospectively reviewed. Treatment strategies included dexamethasone, etoposide, and cyclosporine. Results Survival analysis showed HLH patients with infections other than Epstein-Barr virus (EBV) and unknown causes experienced better 5-year overall survival (OS) than patients with HLH due to autoimmune disease, EBV or immunodeficiency (76% vs. 65, 33.3, 11%, p < 0.001). On multivariate analysis, among all patients, non-response at 8 weeks was the most powerful predictor of poor OS. When treatment response was excluded, hemoglobin < 60 g/L and albumin < 25 g/L at diagnosis were associated with poor OS. In patients with EBV-HLH, hemoglobin < 60 g/L at diagnosis was associated with poor OS. A prognostic risk score was established and weighted based on hazard ratios calculated for three parameters measured at diagnosis: hemoglobin < 60 g/L (2 points), platelets < 30 × 109/L (1 point), albumin < 25 g/L (2 points). Five-year OS of low-risk (score 0-1), intermediate-risk (score 2), and poor-risk (score ≥ 3) patients were 88, 38, and 22%, respectively (p < 0.001). Conclusions These findings indicate that clinicians should be aware of predictive factors at diagnosis and consider 8-week treatment response to identify patients with high-risk of disease progression and the need for second-line therapy and allogeneic HCT.